Avaliação do potencial leishmanicida da própolis vermelha produzida no Bioma Amazônico - GOMES, Louriane Nunes (2023)
Propolis is a substance produced by bees that presents several biological activities, including antimicrobial and anti-inflammatory properties. In the Brazilian Amazon, there is a great diversity of plant species that favor apiculture and the production of bee products such as propolis. Recently, a variety of red propolis was identified in the Amazon biome, presenting promising potential for therapeutic applications, especially in the treatment of neglected diseases such as leishmaniasis. This propolis contains a high concentration of isoflavonoids, particularly the isoflavone calycosin, which serves as its chemical marker. Leishmaniasis is a tropical disease caused by protozoan parasites belonging to the genus Leishmania and transmitted through the bites of infected mosquitoes. Leishmaniasis disease represents a serious public health problem worldwide, especially in developing countries where treatment options are limited and drug resistance is common. In the present study, we evaluated the leishmanicidal activity of a fraction red propolis from the Brazilian Amazon against L. amazonensis, one of the main causes of cutaneous leishmaniasis, in in vitro assays. The results showed that the chloroform fraction of the propolis presented direct activity on promastigote and axenic amastigote forms of L. amazonensis, inducing apoptosis as a mechanism of cell death. In addition, the red propolis presented low toxicity to normal cells, indicating promising potential as a source of new antileishmanial compounds. Red propolis may offer a viable and safe alternative as a source of new compounds with leishmanicidal activity and lower toxicity to normal cells.